Preferensi Pasien sebagai Media Menuju Loyalitas, Dampak Dari Implementasi Relationship Marketing - Vitasya Nusantari; Wekadigunawan Wekadigunawan; Rokiah Kusumapradja (Syntax Corporation Indonesia, 2021)
Patient loyalty is the hope of all health care providers especially hospitals. This certainly must begin with the differentiation strategy of the hospital so that the patient's tendency arises to choose and always reuse the hospital of their choices. This study aims to analyze the relationship between Relationship Marketing, patient preferences for the choice of treatment and its relationship with the formation of loyalty thereafter. With the background of this research is to determine the tendency of patients in choosing a place of treatment with marketing strategies implemented by hospital management in the form of a more personal approach that focuses on the needs and care for patients with the hope of making patients loyal to the hospital. The study was conducted in 2019, at Hospital X in DKI Jakarta Province, located on Jalan Salemba Tengah, Kec. Senen, Jakarta Pusat. The population in this study was adult patients confined to general outpatients at X Hospital at a certain time, using a purposive sampling method. The number of samples using the Slovin formula were 245 respondents. This study uses the Structural Equation Model (SEM) method with the statistical program SmartPLS version 3.0. By proposing 4 hypotheses and with the results all hypotheses are accepted. The results of this study indicate that patient preferences are proven to mediate the relationship between relationship marketing and patient loyalty at Hospital X with management implications that the tendency of patients to choose hospitals is because of the flexibility of patients to provide input, suggestions for the progress of Hospital X, so that patients feel care and respect and this makes the patient remain loyal to continue to choose Hospital X as a place for treatments